Impact of Plasma-Activated Water (PAW) on Seed Germination of Soybean. (29th December 2021) - Guragain, Rajesh Prakash; Pradhan, Suman Prakash; Baniya, Hom Bahadur; Pandey, Bishnu Prasad; Basnet, Niroj; Sedhai, Binita; Dhungana, Santosh; Chhetri, Ganesh Kuwar; Joshi, Ujjwal Man; Subedi, Deepak Prasad
Abstract : The present study reports the generation of plasma-activated water (PAW) using dielectric barrier discharge (DBD), its physicochemical properties, and its potential impact on the seed germination and seedling growth of soybean. The results revealed significant changes in physical parameters, such as pH, total dissolved solids, total suspended solids, turbidity, conductivity, dissolved oxygen, and chemical parameters, such as calcium, chromium, sodium, manganese, nitrate, nitrites, phosphorus, and sulfur and biological parameter such as E. coli in water after plasma treatment. The concentration of dissolved oxygen, conductivity, nitrate, nitrite, and sulfur was increased with an increase in water treatment time, and the amounts of the other analyzed parameters decreased with the increase in water treatment time. The effects of untreated water and plasma-activated water treated for 20 minutes on soybean germination and growth were studied. The germination rate was found to be higher with plasma-treated water. Shoot lengths, seedlings length, vigor index, and germination rates were increased as compared to those germinated by normal water irrigation. The seedlings irrigated with PAW responded to the abundance of nitrogen by producing intensely green leaves because of their increased chlorophyll a as compared to seedlings irrigated with normal water. However, the content of chlorophyll b and carotenoids was found to decrease in the case of seedlings irrigated with PAW. Based on this report, we conclude that PAW could be used to substantially enhance seed germination and seedling growth.